1999
DOI: 10.2355/isijinternational.39.760
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Aluminum and Oxygen Contents in Liquid Iron in Equilibrium with .ALPHA.-Alumina and Hercynite.

Abstract: Experiment and ApparatusThe apparatus used in the present experiments is equlpped with a vertical LaCr03 resistance furnace and a quenching vessel and is shown in Fig. 2 Fig. 6. In Fig. 6

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 0 publications
1
7
1
Order By: Relevance
“…The present authors suggest that aluminum content at critical point is much lower than the reported results [33][34][35] as shown in Fig. 1.…”
Section: Introductioncontrasting
confidence: 54%
See 3 more Smart Citations
“…The present authors suggest that aluminum content at critical point is much lower than the reported results [33][34][35] as shown in Fig. 1.…”
Section: Introductioncontrasting
confidence: 54%
“…1. The oxygen content at the critical point was close to 0.074 mass% O, 30) 0.079 mass% O, 31) 0.0623 mass% O, 32) 0.0574 mass% O, 33) 0.074 mass% O 34) and 0.072 mass% O 35) in the literatures. However, reported aluminum content does not agree with the literatures.…”
Section: Equilibrium Amongmentioning
confidence: 99%
See 2 more Smart Citations
“…The various experimental values for this minimum differ significantly, however. Furthermore, Wasai et al [10] studied the three phase equilibrium liquid iron, Al2O3 and FeO.Al2O3 and compared with previous experimental data. They observed that the oxygen content increases in the low aluminum content region, as already previously noted by Gustafsson and Melberg [13], with substantial deviation from the usually accepted solubility product.…”
Section: Experimental Datamentioning
confidence: 99%